Exploring phytochemical, antioxidant, and antimicrobial properties of Plumeria pudica Jacq. leaves - Kavan Shukla; Kunal N. Odedra; B. A. Jadeja (Scientific Reports)
Abstract Since the emergence of the coronavirus disease, there has been a notable surge in demand for herbal remedies with minimal or no adverse effects. Notably, existing vaccines and medications employed in its treatment have exhibited significant side effects, some of which have proven fatal. Consequently, there is an increasing focus on pharmacological research aimed at identifying optimal solutions to this challenge. This shift entails exploring organic alternatives to traditional medicines, involving the extraction of superior phytochemicals from plants for enhanced biomedical applications in treating various diseases and conditions. To evaluate the qualitative phytochemicals and the quantity of these phytochemicals present in the leaf extracts of the medicinally important plant Plumeria pudica Jacq. Also, the antioxidant property estimation and the study of the antimicrobial properties of the plant have been done in this research. The qualitative phytochemical analysis was done to evaluate the presence of various phytochemicals and to quantify these phytochemicals total content estimation of them was done. Also, phytochemical analysis was further enriched by LCMS-QTOF analysis for the presence of compounds. The determination of the antioxidant potential of the leaves was done by two assays, the reducing power assay and the DPPH(2,2-diphenyl-1-picrylhydrazyl) assay. With that the antimicrobial properties of the leaves were also put to test against four bacterial strains namely, Kocuria rhizophila, Pseudomonas aeruginosa, Klebsiella pneumonia, and E. coli. The results of the phytochemical evaluation indicated that both IPA and hydroalcoholic extracts exhibited a superior phytochemical composition, emphasizing the higher extractive potential of IPA compared to the non-polar petroleum ether extract. The quantitative analysis revealed the predominance of IPA extract as the quantity of phenols (101 mg GAE/g dry-weight of plant extract), flavonoids (402.2 mg QE/g dry-weight of plant extract), carbohydrates (336 mg GLU/g dry-weight of plant extract), and proteins (164 mg BSAE/g dry-weight of plant extract) were highest in the IPA extract. LC–MS QTOF analysis demonstrated the presence of significant phytocompounds in all leaf extracts that have pharmacological applications. Moreover, in antioxidant assays, the IPA extract showed the highest DPPH scavenging activity (66.85% of inhibition), with an IC50 value of 33.54 µg/mL, and the IPA extract exhibited the highest reducing power (1.5 absorbance), signifying robust antioxidant activity. Furthermore, the antimicrobial evaluation revealed that the aqueous and hydroalcoholic extracts displayed larger zones of inhibition compared to the other leaf extracts. And, during the antimicrobial activity interestingly most susceptibility was shown by Klebsiella pneumonia. This study concludes that the diverse extracts of P. pudica leaves possess remarkable phytoconstituent properties both qualitatively and quantitatively, suggesting their rich bioactive compound content and potential as novel sources for therapeutic applications.